STRUKTUR MELODIK BAHASA INDONESIA - . Sugiyono (Universitas Muhammadiyah Surakarta, 2007)
The study describes the melodic structure of Indonesian language carried outin two experiments: (1) the productive experiment which is to measure acousticfeatures of declarative and interrogative statements and (2) the perceptive experiment,to measure the sensibility of the Indonesian speakers in listening speech. Thetwo experiments were conducted by using the approach of experimental and psychoacousticphonetics. The result showed that Lindbom’s (1990) hypo-hyper theoryexplaining the relation between speech production and perception in communication,cannot fully be accepted. The first experiment was significant in at least threeacoustic features: fundamental frequency (F0) of the final note peak, of final mark,and the position of final note peak (Pa) in contour; however, the three parametershave not necessarily to occur altogether to expect the interrogativeness perception.The two characteristics of F0: the height of F0 Pa and the final mark shouldoccur at the same time, whereas the features of final note peak (Pa) was not neededto expect the interrogativeness perception. In short, the interrogative perception ofspeech does not require more complete acoustic features when compared to theirproductive parameters.